Principles and Duties of the State in the View of Islamic Scholars Between the Centuries (4-7 AH/10-13 AD) - Muhammed Tahssen Hussein; Ako Burham Muhammed (Zanco Journal of Human Sciences, 2026)
From the fourth to the seventh centuries AH (10th-13th centuries CE), Islamic scholars emphasized that the basic principle of the state was to achieve justice, enforce Sharia law, and serve the public interest of Muslims. The duties of the state among Islamic thinkers during this period include: protecting the religion, enforcing certain punishments (al-hudud and al-qisas), collecting and distributing zakat, maintaining security, organizing the judiciary, and providing basic services such as education and assistance. This is based on the principle of consultation. Because, according to Muslim thinkers, the Islamic state embodied a legal and civil need to protect both religion and secular life. For Islamic thinkers, the basic principles of the state are justice and equality, which is the basis of governance in the Islamic state, rejecting injustice and corruption, ensuring the implementation of rights for all. In addition to building bridges of cooperation with others, rejecting tribalism and protecting human dignity, the state is also responsible for spreading knowledge, educating people and observing religious duties. At this stage, the state was not only a political entity, but also a religious and civil necessity aimed at ensuring the establishment of religion, organizing the life of the nation, embodying the values ​​of justice and consultation, and providing education and livelihood. This is why Islamic political thinkers paid attention to the state and its duties during this period. The main purpose of this study is to show how the state is run by Islamic scholars and the methods of state administration. The purpose of this study is also to highlight the duties of the state towards society and its subjects.